2017
DOI: 10.1080/19420862.2017.1333212
|View full text |Cite
|
Sign up to set email alerts
|

Impact of S-sulfocysteine on fragments and trisulfide bond linkages in monoclonal antibodies

Abstract: The quality of recombinant proteins such as monoclonal antibodies produced using Chinese hamster ovary cell-based mammalian systems is dependent on many factors, including cell line, process and cell culture media. Due to these factors, the generated product is heterogeneous and may have chemically-induced modifications or post-translational modifications that affect antibody stability, functionality and, in some cases, patient safety. This study demonstrates that S-sulfocysteine, a cysteine derivative, can in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 23 publications
(37 reference statements)
2
14
0
Order By: Relevance
“…A defective disulfide bond network has been reported to introduce different charge to mAbs (Bloom et al, 1997; Gevondyan et al, 2006; Gu et al, 2010; Schauenstein et al, 1986; Seibel et al, 2017; Wang et al, 2018). Although mAb charge variants have been characterized and described in the literature, insights to the underlying mechanisms of their generation would be beneficial in controlling mAb charge variants in industrial production processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A defective disulfide bond network has been reported to introduce different charge to mAbs (Bloom et al, 1997; Gevondyan et al, 2006; Gu et al, 2010; Schauenstein et al, 1986; Seibel et al, 2017; Wang et al, 2018). Although mAb charge variants have been characterized and described in the literature, insights to the underlying mechanisms of their generation would be beneficial in controlling mAb charge variants in industrial production processes.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were subjected to a combined Lys‐C/tryptic digest as described previously (Seibel et al, 2017). For analysis of free thiols, half of the Lys‐C/tryptic digest was reduced by addition of 4.4 µl 0.64 M Tris‐(2‐carboxyethyl)‐phosphin (Roth) and incubation for 30 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of S‐sulfocysteine in feed solutions was hypothesized to reduce the production of hydrogen sulfide by protecting thiol groups against oxidation. In an additional study, the same lab reported that this compound could also lower antibody low molecular weight species and trisulfide bond levels by decreasing free hydrogen sulfide in the medium (Seibel et al, ).…”
Section: Medium Development Approaches To Limit Oxidative Stressmentioning
confidence: 99%